Determinants of growth differentiation factor 15 plasma levels in outpatients with peripheral arterial disease - Emma Skau; Philippe Wagner; Jerzy Leppert; Johan Ärnlöv; Pär Hedberg (Upsala Journal of Medical Sciences)
Background: Growth differentiation factor 15 (GDF-15) is a robust prognostic biomarker in patients with cardiovascular (CV) disease, and a better understanding of its clinical determinants is desirable. We aimed to study the associations between GDF-15 levels and traditional CV risk factors, indicators of atherosclerotic burden, and cardiac geometry and dysfunction in outpatients with peripheral arterial disease (PAD). Methods: An explorative cross-sectional study (Study of Atherosclerosis in Vastmanland, Västerås, Sweden) included 439 outpatients with carotid or lower extremity PAD. The mean age was 70 years (standard deviation [SD] 7), and 59% of the patients were men. Plasma levels of GDF-15 were obtained along with potential determinants, including medical history, biochemical data, echocardiographic measures of cardiac geometry and function, ankle-brachial index (ABI), and carotid ultrasonographic data on intima-media thickness (IMT) and occurrence of carotid stenosis. The relations between GDF-15 concentrations (transformed with the natural logarithm) and the different determinants were evaluated using uni- and multivariable linear regression models. All pre-specified variables were included in the multivariable models. Results: The multivariable analysis identified independent relations of GDF-15 with several of the included variables (adjusted R2 = 0.48). Diabetes (beta coefficient [β] of 0.37, 95% confidence interval [95% CI] 0.25 to 0.50), low-density lipoprotein (LDL) cholesterol (β = −0.22, 95% confidence interval [CI]: −0.34 to −0.09), and physical activity (β = −0.16, 95% CI: −0.25 to −0.06) had the strongest associations. In contrast, no significant independent associations with GDF-15 level were observed for cardiac geometry and function, ABI, IMT, or carotid stenosis. Conclusions: Circulating GDF-15 is more strongly associated with traditional CV risk factors, especially diabetes, LDL cholesterol, and physical activity than with specific indicators of atherosclerotic burden or cardiac dysfunction. To better understand the pathophysiological role of GDF-15 and its link to clinical outcomes in patients with PAD, future studies should focus on the metabolic processes involved in atherosclerotic disease.